Designing supramolecular pastes by controlling host–guest dynamics in reconfigurable networks - Jinrong Wang; Weibin Lin; Valeriia O. Nikolaeva; Rukhma Javaid; Niveen M. Khashab (Nature Communications)
Abstract Stimuli-responsive phase transitions endow smart systems with adaptive functionalities, yet reversible paste-to-gel transitions remain largely unexplored. Here, we report a protonated trianglamine (TA)-based supramolecular paste, in which competitive supramolecular interactions—host–guest binding and electrostatic forces—drive the formation of a dynamic TA–clay–polymer ternary network with paste-like rheology. The material exhibits reversible paste-to-gel transitions under mild thermal stimuli, enabling shape reprogramming, temperature-triggered self-healing, and shape fixation. DFT calculations and molecular simulations reveal the molecular basis of the host–guest interactions in guiding network dynamics and healing behavior. Furthermore, incorporating graphene as conductive filler renders the paste functions as a stretchable, self-healing conductive wire, with potential in flexible electronics and responsive devices. This work introduces supramolecular pastes as a versatile class of smart materials that go beyond traditional hydrogels in structural adaptability and multifunctionality.